Hb J- Meerut [α 120 (H3) Ala ->Glu (α1)] In A Turkish Male (International Journal of Medical Sciences, 2006)
Hb J Meerut is an infrequently found α-globin variant. It has previously been reported in various populations around the world. One particular case reported in 1994 included a Turkish family. In this report, details of a second case of Hb J Meerut in a Turkish male who is unrelated to the first family are described. In the present case a slight increase in the oxygen affinity of Hb J Meerut, relative to that of the normal control, has been observed as detected by low p50 values in arterial whole blood. Additionally, a slight increase in red blood cell count, as compared against a normal individual, was observed.